Impact of Different Aquatic Exercise Programs on Body Composition, Functional Fitness and Cognitive Function of Non-Institutionalized Elderly Adults: A Randomized Controlled Trial - Farinha, Carlos (2021)
Aquatic physical exercise programs have become progressively more popular among elderly people. Some of the major physical exercise program disadvantages on land are minimized due to the specific properties of the aquatic environment. The purpose of the present randomized controlled study is to verify the effects of different aquatic physical exercise programs on body composition, functional fitness and cognitive function in non-institutionalized elderly people. For this study, 102 elderly individuals were randomly allocated into four different groups: AerG (n = 25, 71.44 ± 4.84 years); IntG (n = 28, 72.64 ± 5.22 years); ComG (n = 29, 71.90 ± 5.67 years) and CG (n = 20, 73.60 ± 5.25 years). Individuals from the groups AerG, IntG and ComG participated in three different aquatic physical exercise programs for a period of 28 weeks. The CG participants kept to their usual routines. All participants were evaluated for body composition, functional fitness and cognitive function at two time moments, i.e., pre-(M1) and post-intervention (M2). Significant differences for body composition were found between M1 and M2 for FM (p < 0.001), LBM (p < 0.001) and WCir (p < 0.01) in the AerG, for BMI (p < 0.05), FM (p < 0.05), LBM (p < 0.001) and LCir-R (p < 0.05) in the IntG, and for WGT (p < 0.01), FM (p < 0.05), LBM (p < 0.01), LCir-R (p < 0.05) and LCir-L (p < 0.01) in the ComG groups. For functional fitness, differences were found between M1 and M2 for 2m-ST(p < 0.000), 30s-CS (p < 0.000), 30s-AC (p < 0.05), HG-T-R (p < 0.000) and HG-T-L (p < 0.000) in the AerG, for 2m-ST (p < 0.05), BS-R (p < 0.05), 30s-CS (p < 0.000), 30s-AC(p < 0.01), HG-T-R (p < 0.000) and HG-T-L (p < 0.000) in the IntG, and for 30s-CS (p < 0.000), HG-T-R (p < 0.000) and HG-T-L (p < 0.000) in the ComG groups. The present study evidenced the beneficial effects of physical exercise in an aquatic environment on body composition, functional fitness and cognitive function in non-institutionalized elderly adults. The ComG water-based exercise program showed more beneficial effects in the improvement of body composition and cognitive function variables, while the IntG and AerG programs were more effective in the improvement of functional fitness. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.